KNOWLEDGE DESCRIPTION OF AMENORRHOEA LACTATION METHOD IN BREASTFEEDING MOTHERS IN THE SOKO SUB-DISTRICT HEALTH CENTER WORKING AREA IN TIKUNG DISTRICT LAMONGAN REGENCY - Mardhika, Amellia (Journal of Vocational Nursing, 2020)
Introduction: The Lactation Amenorrhoea Method or MAL is contraception that relies exclusively on breastfeeding or breast milk. From the initial survey the study found 40% of those who had not participated in Family Planning or Family Planning, and 60% who had taken the Pill and Injections. The aim of the study was to describe the knowledge of MAL in nursing mothers in the Soko Sub-District Health Center Working Area, Tikung Subdistrict, Lamongan Regency. Methods: This study used a descriptive design, with a population of 40 people and a sample of 30 people. The sampling used was Consecutive Sampling. Data collection with questionnaire sheets, after the data collected is done Editing, Coding, Tabulating, Scoring, percentage of data then analyzed descriptively data. Results: Based on the results of research on knowledge of breastfeeding mothers about MAL, most (53.3%) had insufficient knowledge, and a small percentage (6.7%) had good knowledge. The conclusion of this study is that most nursing mothers have less knowledge about MAL. Conclusion: The conclusion of this study is that most breastfeeding mothers have less knowledge about the Lactation Amenorrhoea Method or MAL.